Mascara (Wahroonga, N.S.W. : Mascara Poetry, 2007)
"Mascara is an online journal seeking to promote poetry of excellence and originality. We are especially interested in the work of contemporary Australasian and Indigenous poets. Our criteria for selection are quality of image, language and innovation. The word 'mascara' entered the English language in 1890. It derives from Spanish, Arabic and French origins, its meaning evolving from the word mask, masquerade, to darken, to blacken. The Arabic word 'maskhara' means buffoon."
Also known as Mascara Literary Review.
Title from title screen (viewed on 4 May 2009)
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://www.mascarapoetry.com
Selected for archiving
Keywords: Aboriginal Australians -- Poetry; Australian poetry